Exploring the use of the Silent Way Method Using Cuisenaire Rods in Teaching Vocabulary at SD Negeri 091608 Sinaksak - Winata, Femy Chandra; Sembiring, Ribby Violin; Sitepu, Dhea Natasya; Herman, Herman (AMK : Abdi Masyarakat UIKA, 2025)
This study aims to improve the English vocabulary mastery of fifth-grade students at SD Negeri 091608 Sinaksak through the application of the Silent Way method using Cuisenaire Rods. The main problem faced by the students was their limited vocabulary and lack of confidence in using it actively. The subjects of the study were 20 fifth-grade students. The instruments used included vocabulary tests, observation sheets, documentation of the learning process, and teaching media in the form of Cuisenaire Rods to support the implementation of the Silent Way method. The results showed that the Silent Way method with the help of Cuisenaire Rods was quite helpful in enabling students to recognize and remember the vocabulary taught. However, the effectiveness of this method was hindered by the minimal verbal interaction during the learning process, as the teacher relied solely on gestures and visual aids without much spoken explanation. This caused confusion among several students in understanding the context of vocabulary usage. Therefore, the Silent Way method is not fully effective for vocabulary instruction at the elementary school level without adequate verbal support and adjustments.